2002
DOI: 10.1161/01.cir.0000033117.39335.df
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Expression of Cardiotrophin-1 in Failing Human Hearts Is Accompanied by Diminished Glycoprotein 130 Receptor Protein Abundance

Abstract: Background-Cardiotrophin-1 (CT-1), a member of the interleukin-6 superfamily, is a potent inducer of cardiomyocyte hypertrophy that prolongs myocyte survival. Although cardiac CT-1 gene expression is known to be upregulated in some animal models of congestive heart failure, the activation state of the CT-1 system in patients with congestive heart failure is unknown. Methods and Results-This study was designed to determine left ventricular expression of CT-1 and its glycoprotein 130 (gp130)/leukemia inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
53
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 15 publications
9
53
0
3
Order By: Relevance
“…■ Changes in myocardial expression of the IL-6 type family of cytokines Intriguingly, not only systemic levels of IL-6 type cytokines and sgp130 are elevated in cardiovascular disease but also the local gp130-STAT3 signaling cascade is altered at every level in the failing human heart [28, 67,68,113,175]. For instance, it is known that both CT-1 and LIF are increasingly expressed in the failing left ventricular myocardium.…”
Section: General Overview On Gp130 Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…■ Changes in myocardial expression of the IL-6 type family of cytokines Intriguingly, not only systemic levels of IL-6 type cytokines and sgp130 are elevated in cardiovascular disease but also the local gp130-STAT3 signaling cascade is altered at every level in the failing human heart [28, 67,68,113,175]. For instance, it is known that both CT-1 and LIF are increasingly expressed in the failing left ventricular myocardium.…”
Section: General Overview On Gp130 Signalingmentioning
confidence: 99%
“…On the other hand myocardial levels of IL-6 and LIF receptor appear to be reduced in patients with dilative cardiomyopathy [28,67]. Interestingly, while the gp130 receptor was found to be hyperphosphorylated [113], gp130 protein expression is not altered [113] or even diminished in the failing left ventricular myocardium [175]. Expression and phosphorylation levels of STAT3 [52,113], the major downstream signaling molecule of IL-6, as well as phosphorylation of its upstream activators JAK2 and TYK1 is severely reduced in failing hearts of different etiology [113].…”
Section: General Overview On Gp130 Signalingmentioning
confidence: 99%
“…Although the ligand-binding IL-6R alone is not capable of signal transduction, the signaling component gp130 is also involved in the transduction of signals from other ligands of the IL-6 family. When IL-6 is induced by sustained β-adrenoceptor activation, the capacity for signal transduction by IL-6 is probably maintained, because: (a) we found no lowering in the myocardial mRNA expression of IL-6R or gp130 in any model with sustained β-adrenergic activation; (b) in cardiomyocytes, isoproterenol causes a delayed activation of STAT3 (a hallmark of gp130-dependent signal transduction), which can be attenuated by an IL-6-neutralizing antibody (6); and (c) in failing human myocardium, other studies have demonstrated phosphorylation of gp130 and of downstream signaling components (STAT1, STAT3) (24,25).…”
Section: Relevance Of β-Adrenoceptor-mediatedmentioning
confidence: 99%
“…Further study showed that CT-1 caused both enhanced survival and hypertrophy of differentiated cardiac muscle cells and inhibited cardiac myocyte apoptosis after serum deprivation or cytokine stimulation (25,30,36,37,40). CT-1, acting through the gp130 receptor common to the IL-6 family, has been reported to be critical in the induction of hypertrophy in response to biomechanical overload and is overexpressed in cardiomyopathy, as part of a panel of "fetal" genes induced in response to damage (14,28).…”
mentioning
confidence: 99%